(untitled) (Orfeu, 2023)
This work is part of a doctoral research that had as general objective to investigate the existing relations between Special Music Education and the development of social communication in autistic children. Among the products arising from that research, there was the development of an Organizing Protocol for Special Music Education (PROEME), consisting of five steps, which can be used by music educators who work in Special and/or Inclusive Music Education, and which will be presented in this text. The protocol steps – (1) student assessment; (2) prerequisite check; (3) implementation of routines and rules; (4) taking advantage of strengths and difficulties and (5) promoting adaptations – were tested during classes given to autistic children participating in the doctoral study in question. Such steps proved to be very useful for organizing teaching planning, as well as being effective in achieving the outlined pedagogical objectives, with the possibility of application to other deficiencies in general. Armed with techniques and methods, such as those proposed here by PROEME, we believe that the teacher’s work with students with disabilities can become clearer and more effective, as well as less threatening.